Aplicación del Balanced Scorecard para medir la gestión recursos de la empresa Agroinversiones Industriales S.A.C del distrito de Trujillo - periodo 2018 - Fernández Barreto, Lucy Ioany (2019)
The purpose of this research is to propose the application of the Balanced Scorecard as an information tool on the management of resources of the Agroinversiones Industriales INC, with the purpose of determining the fulfillment of objectives and goals set by the company for its growth, as well as for provide information in a timely manner in decision making. The problem was how the application of the Balanced Scorecard influences the resource management of the Agroinversiones Industriales INC. of the district of Trujillo in the period 2018. The inductive-deductive method was used and techniques such as interviews, surveys, other and data collection instruments were used as internal documents of the company. The population for the present work is the Company Agroinversiones Industriales INC and the sample is constituted by the financial information of the company of the period 2018. The application of the Balanced Scorecard was determined in a simple and understandable manner, positively influencing the management of resources of the Agroinversiones Industriales INC, since it has allowed to give importance to both non-financial and financial resources, identifying indicators according to real needs of the company and to take knowledge of the situation of the company, with what management tools it counts, to know that the workers know so much, the mission, vision and objectives of the company, and on that basis to be able to realize a design of scorecard most suitable integral. Also, the present investigation allowed to determine other important factors that affect the implementation process such as: the commitment of senior management and the awareness of the staff.